Faktor-Faktor yang Mempengaruhi Pemakaian Jilbab di Kalangan Mahasiswi Universitas Swadaya Gunung Jati Kota Cirebon - budiyanti, setia (Universitas Islam Negeri Raden Intan Lampung, 2017)
Islam represent the religion having system aqidah arranging all religious service to Allah of SWT and fellow being. Perhaps the inclusive of in it dressy rule for people islam more special for Muslimah. Dress muslim is obligation for Muslimah in running syari'at Islam that is close aurat. This research aim to to know the factor influencing undergraduate in dress muslim and to know the relation dress muslim with the understanding and compliance run the other syari'at Islam. Technique of data collecting use the kuesioner propagated to Self-Supporting University undergraduate of Universitas Swadaya Gunung Jati Cirebon. Result of research obtained by 64% undergraduate which dress muslim have followed the religious education and 36% have never followed the religious education. About 36% undergraduate feel fluent read the Al-Qur'An and 64% undergraduate is not fluent read the Al-Qur'An. There are positive correlation between use jilbab with the other religious service execution. About 36% undergraduate dress muslim influenced by the school, 21% undergraduate dress muslim of because direct understanding of Islam teaching, and fresh 14% undergraduate dress muslim of because parent motivation and environmental.